2016
DOI: 10.4236/ijaa.2016.61006
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review for Quasi-Periodic Oscillations in Neutron-Star Low-Mass X-Ray Binaries

Abstract: In accreting neutron star (NS) low-mass X-ray binaries (LMXBs), the turbulent flow in accretion disk may show magnetic structures. Its emission will vary in time due to inhomogeneous motions through and with the accretion flow. These emissions contribute to considerable X-ray variability on a wide range of timescales in all wavelengths, and down to milliseconds. In this article, we give a brief review for quasi-periodic oscillations (QPOs), one of a periodic X-ray variability, in NS/ LMXBs. Firstly, we give a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 91 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…In the EPIC-pn data, we find a prominent narrow feature at ∼8 mHz, resembling a QPO (see, e.g., Wang 2016, for a recent review), while the broad-band noise is characterized by four zero-centered Lorentzians (L 1 -L 4 ). In the harder NuSTAR band, the broad-band noise has a similar shape, while the narrow 8 mHz feature disappears, substituted by a narrow weak feature at roughly double its frequency (QPO 2 in Table 2 with rms 7%) and by a broader component at a slightly lower frequency (6 mHz).…”
Section: The Timing Analysismentioning
confidence: 73%
“…In the EPIC-pn data, we find a prominent narrow feature at ∼8 mHz, resembling a QPO (see, e.g., Wang 2016, for a recent review), while the broad-band noise is characterized by four zero-centered Lorentzians (L 1 -L 4 ). In the harder NuSTAR band, the broad-band noise has a similar shape, while the narrow 8 mHz feature disappears, substituted by a narrow weak feature at roughly double its frequency (QPO 2 in Table 2 with rms 7%) and by a broader component at a slightly lower frequency (6 mHz).…”
Section: The Timing Analysismentioning
confidence: 73%
“…Initially, we looked at observations that contained a QPO detectable in most energy bands and confirmed that the frequency of the kHz QPO in different bands is consistent with being the same, within the chosen frequency intervals, during the same observation. This is an important information to investigate the nature of kHz QPOs (Mukherjee & Bhattacharyya 2012;Wang 2016). In Fig.…”
Section: The Conditional Distributions Of the Rms Amplitude Vs Qpo Fmentioning
confidence: 99%
“…Twenty years after the discovery of kilohertz quasi-periodic oscillations (kHz QPOs, Strohmayer et al 1996;van der Klis et al 1996) in neutron-star low-mass X-ray binaries (NS-LMXB), a satisfactory explanation of the origin of these QPOs remains a challenge (Gilfanov et al 2003;Mendez 2006;de Avellar et al 2013;Barret 2013;Peille et al 2015;Wang 2016;Cackett 2016;Troyer et al 2018). Both the timing and spectral properties of these high-frequency oscillations are likely driven by general relativistic effects (Stella & Vietri 1998Kato 2005), the neutron-star mass and radius , and the physical processes taking 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the MC method to simulate quasi-periodic oscillations (QPOs), which are typical signals in the astronomical timing analysis. In the PSD, QPOs commonly appear as a peak at a certain frequency with a finite width, which can be described as a Lorentzian function (Wang 2016)…”
Section: Qpo Signalsmentioning
confidence: 99%